A calcium- and calpain-dependent pathway determines the response to lenalidomide in myelodysplastic syndromes - Fang, Jing (Nat Med, 2016)
Despite the high response rates of individuals with myelodysplastic syndrome (MDS) with deletion of chromosome 5q (del(5q)) to treatment with lenalidomide (LEN) and the recent identification of cereblon (CRBN) as the molecular target of LEN, the cellular mechanism by which LEN eliminates MDS clones remains elusive. Here we performed an RNA interference screen to delineate gene regulatory networks that mediate LEN responsiveness in an MDS cell line, MDSL. We identified GPR68, which encodes a G-protein-coupled receptor that has been implicated in calcium metabolism, as the top candidate gene for modulating sensitivity to LEN. LEN induced GPR68 expression via IKAROS family zinc finger 1 (IKZF1), resulting in increased cytosolic calcium levels and activation of a calcium-dependent calpain, CAPN1, which were requisite steps for induction of apoptosis in MDS cells and in acute myeloid leukemia (AML) cells. In contrast, deletion of GPR68 or inhibition of calcium and calpain activation suppressed LEN-induced cytotoxicity. Moreover, expression of calpastatin (CAST), an endogenous CAPN1 inhibitor that is encoded by a gene (CAST) deleted in del(5q) MDS, correlated with LEN responsiveness in patients with del(5q) MDS. Depletion of CAST restored responsiveness of LEN-resistant non-del(5q) MDS cells and AML cells, providing an explanation for the superior responses of patients with del(5q) MDS to LEN treatment. Our study describes a cellular mechanism by which LEN, acting through CRBN and IKZF1, has cytotoxic effects in MDS and AML that depend on a calcium- and calpain-dependent pathway.